2022
DOI: 10.1039/d1qm01503f
|View full text |Cite
|
Sign up to set email alerts
|

Stacking-dependent tetracolour luminescence and mechanofluorochromic properties of an isoquinoline derivative with aggregation-induced emission

Abstract: Although nearly one-third of organic compounds have polymorphism, more than three polymorphs with definite crystalline structures in an organic molecule are very rare. Herein, an aggregation-induced-emission-active isoquinoline derivative containing ethyl...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Among many luminescent molecules [1–4], organic materials with mechanofluorochromic (MFC) behaviours have attracted numerous interest [5–10] because of their unique potential applications in fields of organic light‐emitting diodes [11], security papers [12], mechano‐sensors [13], and memory devices [14]. To date, a great amount of effort has been devoted to the design and synthesis of materials with MFC characteristics, including the derivatives of isoquinoline [15], tetraphenylethylene [16], carbon nanodots [17], 9,10‐distyrylanthracene [18], azaanthracence [19], naphthalimides [20] and some organic boron‐containing π‐conjugated molecules [7, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Among many luminescent molecules [1–4], organic materials with mechanofluorochromic (MFC) behaviours have attracted numerous interest [5–10] because of their unique potential applications in fields of organic light‐emitting diodes [11], security papers [12], mechano‐sensors [13], and memory devices [14]. To date, a great amount of effort has been devoted to the design and synthesis of materials with MFC characteristics, including the derivatives of isoquinoline [15], tetraphenylethylene [16], carbon nanodots [17], 9,10‐distyrylanthracene [18], azaanthracence [19], naphthalimides [20] and some organic boron‐containing π‐conjugated molecules [7, 9].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the intermolecular MFC (inter-MFC) based on reversible changes in molecular orientation and arrangement of dye molecules is superior in durability to the intramolecular MFC (intra-MFC) based on reversible changes in the chemical structures of dye molecules by cleavage and reconstruction of chemical bonds during the grinding–heating process, and thus, the inter-MFC is expected to be applicable to rewritable photoimaging and electroluminescence devices. 8–70 Among various types of fluorescent dyes possessing the mechanofluorochromic properties, donor–π–acceptor (D–π–A)-type fluorescent dyes composed of an electron-donating moiety (D) and an electron-withdrawing moiety (A) connected by a π-conjugated bridge exhibit intense photoabsorption and fluorescence emission properties based on the intramolecular charge transfer (ICT) excitation from the D moiety to the A moiety. 11–33 Thus, the dipole moments as well as photoabsorption ( i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Up to now, isoquinoline-based MFC materials are rarely reported even if isoquinoline is a traditional and good fluorophore. [31,33,34] This luminescent skeleton is obviously ignored compared with tetraphenylethylene, [19,35] anthracene, [36] and cyanoethylene, [37] etc. Recently, our group reported the synthesis of a series of multisubstituted 1-aminoisoquinolines (AIQ, Scheme 1) by an efficient and convenient method from a simple 4H-pyran derivative and secondary amines.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28][29] However, in some cases, it was found that the change of morphology was sometimes not enough to lead to the generation of mechanofluorochromism, revealing the complexity of the formation mechanism. [30,31] Additionally, traditional fluorescence skeletons often contain planar π-conjugated aromatic rings and emit very weak or almost no solid-state fluorescence because of suffering from the effect of aggregation-induced quenching, [32] which greatly limits its development in MFC materials. Although the development of fluorophores with novel chemical structures is fascinating, the construction of new and high-contrast MFC molecules based on the appropriate structural modification of traditional fluorescence skeletons is undoubtedly simpler and more effective.…”
Section: Introductionmentioning
confidence: 99%